Energy saving analysis using burner /thermal tank and heater electric in the marine fuel oil (mfo) treatment process - Kartika, Siska Ayu; Abdullah, N.H.; Saksono, P. (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2023)
Energy savings in Diesel Power Plants (PLTD) have been carried out by comparing the Marine Fuel Oil (MFO) processing process when using a burner/thermal tank and an electric heater. Energy savings are analyzed in this study by calculating the comparison of operational costs, cost efficiency and processing time. The place of research was carried out in one of the Diesel Power Plants in Indonesia, with the object of research being an electric heater and a burner/thermal tank. The research method used quantitative methods in the form of literature study, observation, and field testing. The research was conducted by collecting data on temperature, humidity, and fuel consumption when testing the MFO treatment every 1 hour until the specified temperature was reached 94-96°C. Based on the research results, the processing of MFO using a burner/thermal tank is more efficient in terms of time at the beginning of processing, with a savings of 17.2% and in terms of operational costs more efficient 11.67%. However, after the process continued for 7 days, MFO processing using an electric heater was more efficient in terms of operating costs by 31.87%.